Effects of the rule change from three to five substitutions in the Bundesliga - Alexander Dilger; Lars Vischer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2023)
The COVID-19 pandemic has led to massive restrictions and changes in many areas of life, including professional sports. In football, many games were cancelled and then five instead of three substitutions were allowed with the unchanged maximum of three time-outs. This initially temporary, but now permanent rule change affects the possibilities and thus the decisions of the coaches of the teams. We analyse 836 games with three possible substitutions and 1,000 games with five possible substitutions in the six seasons from 2017/2018 to 2022/2023 of the Bundesliga (first division of German men's football). In addition to team statistics, data on substitutions was collected. The results show that the rule change changed the behaviour of coaches regarding the number of substitutions made and, in some cases, the timing of substitutions. More substitutions generally have a positive effect on the result of the game. – – Die COVID-19-Pandemie hat zu massiven Einschränkungen und Veränderungen in vielen Lebensbereichen geführt, auch im Profisport. Im Fußball wurden viele Spiele abgesagt und danach wurden fünf statt drei Auswechslungen erlaubt bei unverändert maximal drei Auszeiten. Diese zunächst temporäre, nun aber permanente Regeländerung wirkt sich auf die Möglichkeiten und damit auf die Entscheidungen der Trainer der Mannschaften aus. Wir analysieren 836 Spiele mit drei möglichen Auswechslungen und 1.000 Spiele mit fünf möglichen Auswechslungen in den sechs Spielzeiten von 2017/2018 bis 2022/2023 der Bundesliga (erste Liga des deutschen Männerfußballs). Es wurden neben Teamstatistiken vor allem Werte zu den Auswechslungen erfasst. Die Ergebnisse zeigen, dass die Regeländerung das Verhalten der Trainer hinsichtlich der Anzahl der durchgeführten Wechsel und teils bezüglich der Wechselzeitpunkte verändert hat. Mehr Auswechslungen haben grundsätzlich einen positiven Effekt auf das Spielergebnis.
Keywords: Z20; 650; Bundesliga; Football; Ghost Game; Rule Change; Substitution